Learning alphabets using multimedia approach / Norharyati Mat Yaman - Mat Yaman, Norharyati (2005)
The "Learning Alphabet" system is developing through the combination of interactive multimedia element where it uses all elements that will attract kids attention. The interest of developing this application is to bring a new dimension of approach in delivering the teaching method for learning alphabet for kids age 4. This is to make sure that kids can recognize all those alphabets when they entering kindergarten. This report discusses the implementation and the findings of learning alphabet before entering school world as a new approach in interactive multimedia. The letters that were used are created as a 3D image so kids can see the whole shape of those alphabets. In addition, a powerful computer system together with the appropriate multimedia tools is identified in order to fiilfill this system prototype requirement